Promises, Promises : Vote-Buying and the Electoral Mobilization Strategies of Non-Credible Politicians - Hanusch, Marek; Keefer, Philip (World Bank, Washington, DC, 2014)
Vote-buying is pervasive, but not everywhere. What explains significant variations across countries in the greater use of pre-electoral transfers to mobilize voters relative to the use of pre-electoral promises of post-electoral transfers? This paper explicitly models the trade-offs that politicians incur when they decide between mobilizing support with vote-buying or promises of post-electoral benefits. Politicians rely more on vote-buying when they are less credible, target vote-buying to those who do not believe their political promises, and only buy votes from those who would have received post-electoral transfers in a world of full political credibility. The enforcement of a prohibition on vote-buying reduces the welfare of those targeted with vote-buying, but improves the welfare of all other groups in society.